2022
DOI: 10.1021/acs.macromol.1c02034
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Structural, Mechanical, and Reprocessing Properties of Vitrimers Based on a Dynamic Covalent Polymer Network

Abstract: Recyclability and reprocessability of permanently cross-linked polymeric materials have received considerable scientific and technological attention in view of the environmental pollution and sustainable development. By introducing dynamic covalent bonds, vitrimers are emerging as a promising attempt to address this pressing challenge. However, there is still a lack of thermodynamic and kinetic understanding of the bond exchange reactions (BERs) of vitrimers at the molecular level. Herein, by employing coarse-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 71 publications
3
55
0
Order By: Relevance
“…Theoretical studies concerning vitrimers reported in the literature are mainly focused in coarse-grained molecular dynamics simulations, which have been used to study and predict the effect of different parameters, such as the bond swap energy barrier and exchange rate, on the macroscopic properties of these materials. [48][49][50] However, computational studies at the atomic level using density functional theory to study the kinetics of the exchange reaction are scarce. 51 In this work, we aim to use density functional theory (DFT) calculations to render detailed information about exchange kinetics at the level of electrons, that is, the manifestation of electronic structures on the monomer scale, in the pursuit of promising candidates to develop new vitrimeric materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies concerning vitrimers reported in the literature are mainly focused in coarse-grained molecular dynamics simulations, which have been used to study and predict the effect of different parameters, such as the bond swap energy barrier and exchange rate, on the macroscopic properties of these materials. [48][49][50] However, computational studies at the atomic level using density functional theory to study the kinetics of the exchange reaction are scarce. 51 In this work, we aim to use density functional theory (DFT) calculations to render detailed information about exchange kinetics at the level of electrons, that is, the manifestation of electronic structures on the monomer scale, in the pursuit of promising candidates to develop new vitrimeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…Since a large number of chemical modifications may arise, the development of new vitrimers can be accelerated by intensive use of computational chemistry to guide the design of the most promising structures, as opposed to the common trial‐and‐error procedure guided by chemical intuition. Theoretical studies concerning vitrimers reported in the literature are mainly focused in coarse‐grained molecular dynamics simulations, which have been used to study and predict the effect of different parameters, such as the bond swap energy barrier and exchange rate, on the macroscopic properties of these materials 48–50 . However, computational studies at the atomic level using density functional theory to study the kinetics of the exchange reaction are scarce 51 …”
Section: Introductionmentioning
confidence: 99%
“…[19]. This recipe to model swaps has already been able to provide meaningful results in the context of smart vitrimers [20][21][22][23][24], or in the assembly of soft particles [25][26][27].…”
Section: Introductionmentioning
confidence: 95%
“…At present, those kind of systems are still at a research level due to their complex chemistry, expensiveness, long-term stability issues, and nonenvironmental friendliness, among others. , One of the most promising technologies is to introduce dynamic covalent bonds within the polymeric structure that are able to respond to external stimuli, thus creating covalent adaptable networks. , There are already several existing approaches, based on different technologies, such as transesterification, , Diels–Alder adduct chemistry, imine bonds, disulfide bonds, dynamic B–O bonds, hemiaminals/hexahydrotriazines, and acetal linkages, among others.…”
Section: Introductionmentioning
confidence: 99%
“…2,6 One of the most promising technologies is to introduce dynamic covalent bonds within the polymeric structure that are able to respond to external stimuli, thus creating covalent adaptable networks. 7,8 There are already several existing approaches, based on different technologies, such as transesterification, 9,10 Diels−Alder adduct chemistry, 11 imine bonds, 12 disulfide bonds, 13 dynamic B−O bonds, 14 hemiaminals/hexahydrotriazines, 15 and acetal linkages, 16 among others. More specifically, disulfide linkages have been widely used for this purpose since 1990 when Tesoro and Sastri introduced them for the first time into epoxy networks.…”
Section: Introductionmentioning
confidence: 99%